Feasibility and Safety of Endometrial Injection of Autologous Bone Marrow Mesenchymal Stem Cells in Mares - Alvarenga, Marco Antonio [UNESP]; do Carmo, Marcio Teoro [UNESP]; Segabinazzi, Lorenzo Garrido [UNESP]; Guastali, Mydian Daroz [UNESP]; Maia, Leandro [UNESP]; Landim- Alvarenga, Fernanda Cruz [UNESP] (Elsevier, 2016)
Chronic degenerative endometritis (CDE) is an important cause of fertility problems in older mares. It is estimated that 30% of mares breeding are over 18 years old and the high value of their progeny encourages the use of these animals in assisted reproduction procedures. Currently, cell-based therapies are broadly used in human and veterinary regenerative medicine and have been showed a good effect on the treatment of liver fibrosis. Thus, the present study aimed to evaluate the feasibility and safety of endometrial injection of autologous bone marrow MSCs in mares. Mares were examined by transrectal ultrasound and the endometrial stem cells injections performed during diestrous, using injection needles coupled to a teflon catheter through the biopsy channel of a flexible endoscope. After treatment clinical evaluations (heart reat, respiratory rate, staining of the mucosa, capillary refill time, body temperature and lameness score) were performed daily during seven days. The intrauterine fluid and endometrial edema was evaluated before, 24 and 48 hours after the procedure by ultrasonographic exams and the inflammatory infiltrate (polymorphonuclear cells and mononuclear cells) and degree of fibrosis by histological evaluations before (D0) and 15 (D15), 30 (D30) and 60 (D60) days after endometrial injections. The results were evaluated by Kolmogorov-Smirnov and Kruskal-Wallis test followed by Dunn test and for fertility rates was used Chi-square, considering a 5% significance level. Neither clinical alteration was observed in mares after treatment, as well as, intrauterine fluid and endometrial edema were not detected in any mare before and after cell therapy. After cell therapy, significantly more PMNs were found in D15 biopsies, however, these cells were not observed in D30 and D60 biopsies. No worsening on the histological architecture after treatment was observed in any mare. In conclusion, the results of this study showed that endometrial hysteroscopic injections of stem cells in mares is a safe procedure.
Keywords: Endometriosis; Endometritis; Fibrosis; Mare; Stem-cell